Chứng minh đẳng thức:
b) a(b - c) - a(b + d) = -a(c + d)
Chứng minh đẳng thức sau:
a)(a-b)+(c-d)-(a+c)=-(b+d)
b)(a-b)-(c-d)+(b+c)=a+d
Chứng minh đẳng thức sau:
a/ ( a-b) + ( c-d)-( a+c)= -(b+d)
b/ ( a-b )-( c- d) + (b+c) = a+d
chứng minh đẳng thức :
(a+b).(c+d)-(a+d).(b+c)=(a-c).(d-b)
Chứng minh các đẳng thức sau:
a)(a-b)+(c-d)-(a+c)=-(b+d)
b)(a-b)-(c-d)+(b+c)=a+d
chứng minh đẳng thức :
a.(b-c)-a.(b+d)= -a.(c+d)
chứng minh đẳng thức sau:
(a-b)+(c-d)-(a+c)=-(b+d)
Chứng minh đẳng thức sau :
( a - b ) - ( c- d ) + ( b + c ) = a + d
chứng minh đẳng thức:
(a-b-c+d)-(-a-b+c+d) = 2(a-c)